ANALISIS KINERJA AGROINDUSTRI KOPI CAP JEMPOL SUPRI DI KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Senja Naromsyah; Wan Abbas Zakaria; Dian Rahmalia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study aims to analyze the accuracy of raw material procurement, production performance, and marketing strategies of the Cap Jempol Supri Coffee Agroindustry in Kemiling District, Bandar Lampung City.  The research was conducted at the Cap Jempol Supri Coffee Agroindustry located in Kemiling District, Bandar Lampung City, using a case study method.  The respondents included the agroindustry owner, production employees, and packaging employees.  The first objective was analyzed using the 6 Right criteria.  The second objective was analyzed based on eight aspects: productivity, capacity, quality, delivery speed, flexibility, processing speed, packaging process, and production management.  The third objective was analyzed using the 4P method (Product, Price, Place, Promotion).  The results showed that the accuracy of coffee and corn raw material procurement was categorized as good. The lowest score was found in the price indicator because the price obtained did not meet expectations.  Labor productivity was 34.33 kg per workday, machine capacity was 77percent, and product quality reached 85percent. Delivery speed, flexibility, processing speed, packaging process, and production management were also categorized as good based on the analysis.  The agroindustry produces two types of products: blended ground coffee and pure ground coffee, sold in two packaging sizes of 100 grams and 200 grams. The selling price is competitively determined. The products are marketed in Kemiling District and Sukarame District.  Promotion is still carried out through personal selling by directly visiting small shops and wholesale stores to offer ground coffee products for purchase and further distribution. Keywords: Agroindustry, ground coffee, marketing, production performance, raw material